Academic Procrastination and Learning Boredom in Psychology Students - Cahyadi, Wilson Cipta (ANIMA Indonesian Psychological Journal, 2013)
A lot of students still procrastinate despite the apparent negative effects it has. Based on the preliminary survey, procrastination was related to learning boredom. Several earlier studies had similar results. In this study, the author focused on academic procrastination and learning boredom, in order to find the relation between the two variables in psychology students. The subjects were psychology students(N=518), each completed three instruments: Academic Procrastination Instrument (API), Learning Boredom Survey, and Task Utility Survey. Results reveal that academic procrastination has a positive correlation with learning boredom (r = .412 and p = .000), indicating that the psychological aspect has a bigger role in academic procrastination, while the value aspect of Temporal Motivation Theory (TMT) has the highest correlation between academic procrastination and learning boredom. Aside from that, it was also found that most of the psychology students procrastinate and experience learning boredom. Prokrastinasi meskipun memiliki dampak yang buruk tetapi masih tetap banyak mahasiswa yang melakukannya. Dari survei awal diketahui bahwa prokrastinasi memiliki hubungan dengan kejenuhan. Beberapa penelitian sebelumnya juga memberikan hasil yang serupa. Dalam studi ini peneliti memfokuskan pada prokrastinasi akademik dan kejenuhan belajar. Penelitian ini melibatkan 518 mahasiswa psikologi yang menyelesaikan pengukuran melalui tiga instrumen yaitu angket prokrastinasi akademik (API), angket kejenuhan belajar, dan angket utilitas tugas (UT). Hasil penelitian menunjukkan bahwa prokrastinasi akademik memiliki korelasi positif dengan kejenuhan belajar dengan r = .412 dan p = .000. yang menunjukkan bahwa aspek psikologi lebih berperan dalam melakukan prokrastinasi akademik dan dari TMT aspek value yang memiliki korelasi paling besar antara prokrastinasi akademik dan kejenuhan belajar. Selain itu, diketahui bahwa cukup banyak mahasiswa psikologi yang melakukan prokrastinasi akademik dan mengalami kejenuhan belajar.